Tradisi Maimbau Pasinggah Setelah Tunangan di Nagari Batu Palano, Kecamatan Sungai Pua, Kabupaten Agam (Perspektif ‘Urf) - Halimah Tusakdiyah; Muhammad Ridha (Lembaga Yasin AlSys, 2026)
The Maimbau Pasinggah tradition, as part of the customs of Minangkabau society, has received attention in studies of customary law and Islamic law, but research that specifically analyzes its implementation after khitbah from the perspective of ‘urf in Nagari Batu Palano remains limited. This study aims to describe the implementation of the Maimbau Pasinggah tradition after khitbah and to analyze its position from the perspective of ‘urf in the community of Nagari Batu Palano, Sungai Pua Subdistrict, Agam Regency. This study used a qualitative approach with a case study design. The research participants consisted of traditional leaders, the Chair of the Kerapatan Adat Nagari (KAN), religious leaders, Bundo Kanduang, and community members selected using purposive sampling. Data were collected through in-depth interviews, observation, and documentation, and were then analyzed using an interactive analysis model that includes data reduction, data display, and conclusion drawing. The results showed that the Maimbau Pasinggah tradition is still practiced as a hereditary custom aimed at strengthening kinship relations, introducing the prospective bride and groom to the extended family, and preparing them for married life. From the perspective of ‘urf, this tradition contains values of public benefit in social and cultural aspects, but the practice of the prospective bride and groom staying overnight before the marriage contract requires adjustment to align with the provisions of Islamic law. These findings contribute to the development of studies on ‘urf in Islamic family law and broaden understanding of the relationship between Minangkabau customs and sharia principles. The conclusion of this study affirms that the preservation of local traditions needs to be carried out selectively by considering the values of public benefit, customary norms, and the limits of Islamic law.